2013
DOI: 10.1111/dmcn.12117
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of life lived with dystonia inversely correlates with response to pallidal deep brain stimulation in both primary and secondary childhood dystonia

Abstract: Aim The aim of this study was to examine the impact of dystonia aetiology and duration, contracture, and age at deep brain stimulation (DBS) surgery on outcome in a cohort of children with medically refractory, disabling primary, secondary‐static, or secondary‐progressive dystonias, including neurodegeneration with brain iron accumulation (NBIA). Method Dystonia severity was assessed using the Burke–Fahn–Marsden Dystonia Rating Scale (BFMDRS) motor score at baseline and 6 and 12 months postoperatively in a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
122
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 29 publications
(37 reference statements)
3
122
3
1
Order By: Relevance
“…Increasing evidence suggests DBS is successful in reducing childhood dystonia, demonstrating significant improvement on impairment focussed measures, such as the Burke Fahn Marsden Disability Rating Scale 11,12 . However, secondary dystonias appear to be less responsive to DBS compared with primary dystonia 11 , and improvements in motor scores have been shown to be more subtle and not as durable 11 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence suggests DBS is successful in reducing childhood dystonia, demonstrating significant improvement on impairment focussed measures, such as the Burke Fahn Marsden Disability Rating Scale 11,12 . However, secondary dystonias appear to be less responsive to DBS compared with primary dystonia 11 , and improvements in motor scores have been shown to be more subtle and not as durable 11 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…However, secondary dystonias appear to be less responsive to DBS compared with primary dystonia 11 , and improvements in motor scores have been shown to be more subtle and not as durable 11 . Studies have shown that impairment measures have failed to capture the subjective meaning of post DBS changes, or the functional priorities and concerns of parents 13,14 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…From this large range of grouping, an independently driven cluster analysis was able to identified 4 subgroupings. In our previous reported we have pragmatically grouped CAYP with dystonia into categories of "Primary/Primary-plus", "Secondary-Static" and "Secondary-Progressive" [8,9] Remarkably, these categorisations closely resemble the clusters resulting from our present analysis, Cluster 1 comparable to our Primary/Primary-Plus group, Cluster 2 our Secondary-Progressive (AKA heredo-degenerative) group and Clusters 3 and 4 resembling the Secondary-Static dystonia groupings (Cluster 3 due to CP, Cluster 4 due to other causes). Cluster analysis methods provide data driven techniques for identifying subjects across data sets with similar characteristics.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Treatment of spasticity may improve DBS outcomes in long-standing dystonia (Lumsden et al 2013), particularly when supported by occupational and physiotherapies with individualized and goal-directed outcomes.…”
Section: Reportmentioning
confidence: 99%